2012
DOI: 10.3168/jds.2011-4766
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of subclinical mastitis in Dutch dairy heifers in the first 100 days in lactation and associated risk factors

Abstract: Heifer mastitis is a problem and risk factors may differ between heifers and older cows. The aim of this study was to estimate the heifer subclinical mastitis (HSCLM) incidence based on elevated somatic cell count (SCC) in the first 100 d in lactation and the associated risk factors in Dutch dairy herds. In 2008, 173 farmers filled in a questionnaire regarding housing and herd management factors potentially related to udder health. In addition, monthly milk production and SCC data from all cattle were provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 28 publications
6
37
0
2
Order By: Relevance
“…It has also been described in humans as the major cause of nosocomial and community acquired infections (Chaudhary and Payasi, 2013). Most of the organisms isolated from this study have also been reported as either contagious or environmental pathogens that are found in raw milk from different parts of the world (Waller et al, 2011;Hogan et al, 2011;Santman-Berends et al, 2012;Hill et al, 2012;Oliver and Muranda, 2012;Chaudhary and Payasi, 2013). Staphylococcus and Corynebacterium species are considered before as minor pathogens found in milk; but, have now became more common as mastitis causing organisms (Oliver and Muranda, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has also been described in humans as the major cause of nosocomial and community acquired infections (Chaudhary and Payasi, 2013). Most of the organisms isolated from this study have also been reported as either contagious or environmental pathogens that are found in raw milk from different parts of the world (Waller et al, 2011;Hogan et al, 2011;Santman-Berends et al, 2012;Hill et al, 2012;Oliver and Muranda, 2012;Chaudhary and Payasi, 2013). Staphylococcus and Corynebacterium species are considered before as minor pathogens found in milk; but, have now became more common as mastitis causing organisms (Oliver and Muranda, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Salmonella, Listeria, Pseudomonas, Corynebacterium, Campylobacter and Micrococcus species have also been reported in raw milk worldwide (Waller et al, 2011;Hill et al, 2012;Santman-Berends et al, 2012;Bracke et al, 2013). Subclinical mastitis is the most common form of mastitis among dairy cattle (Salvador et al, 2012), with a prevalence of about 40-50 times more than the clinical mastitis (Roy et al, 2009;Mekibib et al, 2010); which attracts for prompt attention in the dairy industry.…”
Section: Ajavsmentioning
confidence: 99%
“…A high prevalence of environmental pathogens is suggestive of poor cleaning and preparation of the udder before milking. Contaminated bedding, dirty environments, and colonisation of teat skin and teat injuries are potential sources of environmental pathogens (Santman-Berends et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Intramammary infections in heifers in early lactation potentially cause severe economic losses (Seegers et al 2003;De Vliegher 2005a) because of detrimental effects on udder development and future production leading to an increased risk of premature removal from the herd (Rupp et al 2000;Waage et al 2000;Oliver et al 2003;De Vliegher et al 2005a;De Vliegher et al 2005b;Santman-Berends et al 2012;Archer et al 2013). The prevalence of subclinical mastitis in heifers varies widely among studies and ranges from 12% to over 57% of quarters infected (Barkema et al 1999b;De Vliegher et al 2001;Bowers et al 2006;Andersen et al 2010;Santman-Berends et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation